Fabrication of degradable carboxymethyl cellulose (CMC) microneedle with laser writing and replica molding process for enhancement of transdermal drug delivery - Park, Yong-Hun; Ha, Sang Keun; Choi, Inwook; Kim, Kyu Sik; Park, Jeryang; Choi, Nakwon; Kim, Bumsang; Sung, Jong Hwan (Biotechnology and bioprocess engineering, 2016)
Transdermal drug delivery system (TDDS) may provide a more reliable method of drug delivery than oral delivery by avoiding gut absorption and first-pass metabolism, but needs a method for efficiently crossing the epidermal barrier. To enhance the delivery through the skin, we have developed a biocompatible, dissolvable microneedle array made from carboxymethyl cellulose (CMC). Using laser ablation for creating the mold greatly improved the efficiency and reduced the cost of microneedle fabrication. Mixing CMC with amylopectin (AP) enhanced the mechanical and tunable dissolution properties of the microneedle for controlled release of model compounds. Using the CMC microneedle array, we observed significant enhancement in the skin permeability of a fluorescent model compound, and also increase in the anti-oxidant activity of ascorbic acid after crossing the skin. Our dissolvable microneedle array provides a new and biocompatible method for delivery of drugs and cosmetic compounds through the skin.